Effect of Problem-based Learning on Mathematical Problem-solving Ability of Sixth-Grade Students in Leshan Primary School - Yu , Yuhua; Saleewong, Danucha; Klangphahol, Kanreutai (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aim: In the 21st century, Mathematics is a science that plays an important role in learners’ education and life. Science helps humans in the analysis of problems and surrounding circumstances that could guide them in prediction, planning, and finding the most appropriate way to solve the problems. The objective of this study was to (1) compare the students’ mathematical problem-solving ability before and after learning through Using Problem-based Learning, (2) compare the mathematical problem-solving ability after learning through Problem-based learning with the determined criterion set at 70%, and (3) assess the significance level of students’ satisfaction after learning through Problem-based Learning Materials and Methods: This study used a cluster sampling method with 30 students as the sample. The research tools are (1) a lesson plan, (2) multiple choice for Mathematical problem-solving ability, and (3) a satisfaction questionnaire. Conduct pre-test and post-test on the sample using academic performance papers, and analyze the mean, standard deviation, and t-test. Results: Results found that (1) the student’s mathematical problem-solving ability after learning through problem-based learning than before at a statistically significant level of .05. (2) The students’ mathematical problem-solving ability after learning through problem-based learning was higher than the determined criterion of 70% at a .05 statistical significance level. (3) The students’ satisfaction after learning through problem-based learning was at a higher level. Conclusion: Through the classroom practice of problem-based learning, the learning efficiency is improved and the individual learning needs of students are met. It helps to improve students' academic performance and win students' popularity.